Produksi Bio - Oil Dari Biomassa Pelepah Sawit Menjadi Bio-Oil Menggunakan Katalis Co/Lempung Dengan Metode Pirolisis - Edwidya Ocktaviani Armay; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Petroleum as source of fossil fuels that were not renewable energy and nearly exhausted while the consumption of energy always have been increase time by time. One of alternative energy that can solve this problem is bio-oil from biomass such as frond palm. Bio-oil can be produced through pirolysis process of frond palm using Co/Clays Cengar. The research purpose is knowing effect of the ratio of catalyst Co/Clays Cengar on yield of bio-oil that produced by pyrolisis process from frond palm. Pyrolysis used biomass 50 gram, silinap 500 ml and Co/Clays Cengar catalyst which variated by 0, 1, 3 and 5% wt on frond palm at 330oC and mixed rotation 300 rpm. The results showed that the maximum yield obtained at the level of developing of a metal catalyst Co 1% of the clay that is equal to 50 %. Thetest results obtained by the physical properties of density 1,0042 g/ml, 10,493 cSt viscosity, acid number of 0,42976 g NaOH/g sample and the flash point is 52º C. The results obtained have characteristics approaching the characteristics of standard fuel oil and bio-oil.Kata Kunci : Bio-oil, Co/Clays Cengar, Frond Palm, Pyrolysis